Application of Simplified Analysis Procedures For Performance-Based Earthquake Evaluation of Steel Special Moment Frames. Issue 4 (November 2015) - Lignos, Dimitrios G.; Putman, Christopher; Krawinkler, Helmut
This paper evaluates the effectiveness of single and multi-mode nonlinear static procedures (NSPs) as well as the FEMA P58 simplified approach versus rigorous nonlinear response history analyses (NRHA) for estimating seismic demands of steel special moment frames (SMFs). This work was mostly conducted within the framework of the ATC-76-6 project and indicates the level to which simplified analysis procedures in combination with commonly used nonlinear component models can reliably predict story-level engineering demand parameters (EDPs) such as, story drift ratios, story shear forces, overturning moments, residual deformations and peak floor absolute accelerations. It is advisable to employ a combination of NSP and NRHA to understand the seismic performance of steel SMFs and quantify important EDPs.